ANALISA KINERJA MESIN OVEN PENGERING BUAH BERKAPASITAS 1 KG - Saputra, Adi (Fakultas Teknik UMRI, 2020)
One way to process pineapples, pineapples are classified as highly perishable and rotten foods. For this reason, it is necessary to handle fruit to save the abundance of fruit that occurs during harvest. One example of what the community has done is dealing with the abundant harvest of pineapples by making fruit as a daily snack, namely getting dry fruit products that are ready to eat by making pineapple chips. The production of fruit kiripik is usually done by frying which is done by frying which contains oil which is usually called conventional frying. Therefore, with this oven drying machine, it can help the community in making pineapple chips. The purpose of this study was to determine the moisture content in the manufacture of pineapple chips in a drying oven machine, to analyze the ratio of temperature settings that were set 95 to 110 in the drying process. The fastest drying time is achieved at drying at a drying temperature of 110 ° C.